2022
DOI: 10.1038/s41558-021-01271-8
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the promise of carbon labelling

Abstract: Carbon labeling systems can inform individual and organizational choices, potentially reducing the carbon footprints of goods and services. We review the ways labeling has been conceptualized and operationalized and available evidence on effectiveness. The literature has focused mainly on how labeling affects retail consumer behavior but much less on how labeling affects the behavior of the organizations that produce, transport, and sell products despite preliminary research suggesting that effects on corporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 105 publications
0
11
0
1
Order By: Relevance
“…Specifically, the present study highlighted that a cross-category traffic-light front-of-pack environmental label that is unique, well understood and informative was effective in reducing the environmental impact of food choices. In real life, meeting all these criteria raises substantial challenges for policy makers, in line with drawbacks previously described for environmental labelling implementation in other sectors [39,40]. First, a unique label voted in by the agricultural and food industry is needed to guarantee its widespread and to allow comparisons between different food products and different food categories.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the present study highlighted that a cross-category traffic-light front-of-pack environmental label that is unique, well understood and informative was effective in reducing the environmental impact of food choices. In real life, meeting all these criteria raises substantial challenges for policy makers, in line with drawbacks previously described for environmental labelling implementation in other sectors [39,40]. First, a unique label voted in by the agricultural and food industry is needed to guarantee its widespread and to allow comparisons between different food products and different food categories.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, they found not only that colored labels were more effective than labels without color, but additionally that a simple TLL was as effective or more effective than more complex labels. In summary, although research has shown that carbon labels can influence purchase decisions see also the reviews of carbon labels by Potter et al (2021), Rondoni and Grasso (2021), Taufique et al (2022) there is, in the words of Thøgersen and Nielsen (2016), "a lack of research on how to increase the effectiveness of such a label by optimizing its design" (p. 87).…”
Section: Behavioral Effects Of Carbon Labelsmentioning
confidence: 99%
“…For example, the Eco Label index 1 alone already lists 455 different eco labels, of which about 35 are carbon labels (and there are still some missing from this list). To distinguish between the different types of carbon labels, several classification systems have been proposed (see Schaefer and Blanke, 2014;Thøgersen and Nielsen, 2016;Meyerding et al, 2019;Lemken et al, 2021;Taufique et al, 2022). Taufique et al (2022), for example, suggested a classification into 4 types of carbon labels: certificate, ordinal rating, quantitative and ordinal plus quantitative rating labels.…”
Section: Introductionmentioning
confidence: 99%
“…Carrying out the LCA is crucial for obtaining the so-called Environmental Product Declaration (EPD) for the product [43]. It is a document that presents a series of data on the resource consumption and environmental impacts in relation to the product's life cycle, namely: In response to the sensitivity to the problem of climate change, many social groups in developed countries are creating product labelling systems informing about the carbon footprint (CF) [44,45]. Placing environmental labels on products and presenting information about the LCA results, is designed to provide consumers with accurate information about the environmental effects of products, facilitating their conscious choice, as well as introducing the factor of competition between different manufacturers of similar products.…”
Section: Evaluation Of Greenhouse Gas Emissions In the Life Cycle Ass...mentioning
confidence: 99%